Áreas de Silencio : 23. Bienal de Arte de Pontevedra. - González-Alegre, Alberto; Museo de Pontevedra, Pontevedra; 23. Bienal de Arte de Pontevedra, 1994 (Pontevedra : Deputación de Pontevedra, 1994)
Álvarez Basso, Dario ; Cáccamo, Berta ; Espona, Xosé ; Goyanes, Antón ; Lamazares, Antón ; Murado, Antonio ; Pacheco, Simón ; Pérez Vicente, Isaac
Áreas de Silencio, 23. Bienal de Arte de Pontevedra, Museo de Pontevedra, Pontevedra, Edificio Sarmiento, Agosto - Setembro 1994
boek